2015
DOI: 10.1080/21711976.2015.1026083
|View full text |Cite
|
Sign up to set email alerts
|

Frugality and psychological wellbeing. The role of voluntary restriction and the resourceful use of resources / Frugalidad y bienestar psicológico. El papel de la restricción voluntaria y el uso ingenioso de recursos

Abstract: This paper analyses the relationship between psychological wellbeing and frugality, evaluated as behaviour geared towards the voluntary restriction of consumption and the resourceful use of available resources. An analysis of structural equations was carried out using a model with moderated mediation on a sample of 1113 people. The main finding was the predictive capacity of frugal behaviour, in its two factors, to explain the level of wellbeing. A mediation effect was observed where the restriction of consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 21 publications
0
9
0
3
Order By: Relevance
“…A "simple lifestyle" was stressed, that is, a deliberately cooperative and austere lifestyle (Corral-Verdugo, 2010). This conception is close to the notion of frugality, relative to voluntary restriction and creative use of resources (Muiños, Suárez, Hess & Hernández, 2015).…”
Section: Pro-ecological Commitmentsmentioning
confidence: 75%
“…A "simple lifestyle" was stressed, that is, a deliberately cooperative and austere lifestyle (Corral-Verdugo, 2010). This conception is close to the notion of frugality, relative to voluntary restriction and creative use of resources (Muiños, Suárez, Hess & Hernández, 2015).…”
Section: Pro-ecological Commitmentsmentioning
confidence: 75%
“…Moreover, environmental knowledge and information (Chan et al 2017;Díaz-Siefer et al 2015; de Frutos and Egea 2011; Yeoh and Paladino 2013), attitude (Singh and Gupta 2013;Sun et al 2014), awe (Yang et al 2018), personality traits (Puente-Diaz and Arroyo 2015), inclusion of nature in the self-gradient (Amérigo et al 2017), recalled pride and guilt (Rowe et al 2019), and perceived uncertainty (Fernando et al 2018) are also found to be significant predictors of sustainable consumption behavior. Behavioral traits like prosocial behavior (Neaman et al 2018), frugality and restriction and consumption (Muiños et al 2015;Yeniaras and Akarsu 2017), and materialism (Evers et al 2018;Goldsmith et al 2014) are also investigated as the antecedents in the sustainable marketing literature.…”
Section: Dominance Of Psychological Variables In Shaping Sustainable mentioning
confidence: 99%
“…The literature on consumer consumption, whether understood as overconsumption [15,16] or sustainable consumption [17,18] has increased dramatically in the past two decades [19], becoming a topic of investigation in a diverse range of disciplines, including ecology [20], economics [21], marketing research [22], sociology [23], and psychology [24][25][26]. Studies have investigated the association between personality traits (e.g., being frugal, materialistic) and sustainable behavior [23,27], while others have looked at how to enhance sustainability by investigating attitudes and values towards the environment [17,18,26]. Several studies have demonstrated that being aware of the environmental impact of consumption is not enough to predict consumption restriction [17,26].…”
Section: Existing Theory and Research On Overconsumptionmentioning
confidence: 99%